The synergistic antibacterial activity and mechanism of ultrasound and hydrogen peroxide against Staphylococcus aureus in water. (December 2022) - Zhu, Yupan; Xu, Hangbo; Yang, Xudong; Zhuang, Jie; Wang, Yanping; Feng, Junxia; Ma, Ruonan; Jiao, Zhen
Abstract: Staphylococcus aureus ( S. aureus ) as an important pathogen with high stress tolerance poses a serious threat to human health. Ultrasound (US) combined with hydrogen peroxide (H2 O2 ) is considered to be a relatively eco-friendly and efficient approach for pollutant degradation in water, but their synergistic antimicrobial effect has been rarely researched. Therefore, this study investigated the synergetic antimicrobial effects and mechanism of US and H2 O2 against S. aureus in water. The results show that US (288 W, 20 kHz) and H2 O2 (0.1, 0.25 and 0.5 M) exhibited marked synergistic antibacterial effects against S. aureus, achieving a bacterial reduction ranging from 0.34 to 7.05 log CFU/mL, which was significantly higher than the individual US (0.05–0.48 log reduction CFU/mL) or H2 O2 (0.06–4.94 log reduction CFU/mL) treatment. The best synergistic effect was achieved by the combined treatment of US and 0.25 M H2 O2 for 6 min (7.05 log reduction CFU/mL). The physiological results show that US combined with H2 O2 could disrupt the cell membrane integrity, alter the cell morphology including cell shrinkage, collapse, and fragmentation, decrease the average cell size and cause cell surface oxidation. More importantly, the enhanced generation of hydroxyl radical (OH) was confirmed to play an important role in the synergistic antibacterial effects of US combined with H2 O2 . These results indicate that the combined treatment of US and H2 O2 is a promising technology to reduce S. aureus counts in water. Highlights: US combined with H2 O2 is a promising method to reduce S. aureus counts in water. The combined treatment of US and 0.25 M H2 O2 for 6 min exhibited the lowest combination index value. US stimulated hydroxyl-radical formation from H2 O2 . US combined with H2 O2 disrupted the cell membrane integrity and caused cell surface oxidation. US combined with H2 O2 altered the cell morphology and decreased the cell size of S. aureus .